Bagaimana Generasi Milenial Mendidikan Diri Mereka Sendiri?: Kajian Harmeneutik Terhadap QS. An-Nahl ayat 70 dan Teori Calljum: - Erlina Farah Agustina; Nasikhin Nasikhin; Mustopa Mustopa (CV. ITTC INDONESIA, 2025)
This study aims to examine the meaning of QS. Specifically, it will examine An-Nahl verse 70 in the context of the self-education of the millennial generation, using a hermeneutic approach and integrating Calljum's theory. A qualitative method with a library research approach was used to analyze QS. The verse is analyzed and related to Calljum's theory in the context of millennial generation self-education. Through hermeneutic analysis, the verse is understood not only textually but also in relation to the phenomenon of